Efektivitas Sistem Pendidikan Anak Migran Indonesia di Sekolah Indonesia Johor Bahru Malaysia - Mary Ismowati; Angga Sulaiman; Alwan Dwi Yanto; Layung Sri Pradonggo; Silvia Balqis (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Effectiveness of the Indonesian Migrant Children's Education System: A Case Study at the Indonesian School of Johor Bahru (SIJB). Tujuan penelitian untuk mengetahui “Efektivitas Sistem Pendidikan Anak Migran Indonesia (Studi di Sekolah Indonesia Johor Bahru)”,  menggali data dari lapangan  bagaimana efektivitas kebijakan Sistem Pendidikan Anak Migran Indonesia (Studi di Sekolah Indonesia Johor Bahru)”. Kebijakan sebagai serangkaian tindakan untuk mencapai tujuan tertentu dalam suatu lingkungan tertentu dengan menunjukkan hambatan dan kesempatan untuk pelaksanaan usulan kebijakan tersebut. Metode penelitian kualitatif, dalam bentuk deskripsi informasi dari para informan di Sekolah Indonesia Johor baru Malaysia. Kesimpulan Sistem Pendidikan Anak Migran Indonesia di Sekolah Indonesia Johor Bahru (SIJB) telah efektif hal ini ditinjau dari 5 ( lima) dimensi Efektivitas telah terpenuhi :  pertama sasaran yang hendak dicapai sudah terpenuhi. Sekolah Indonesia Luar Negeri (SILN) khususnya di SIJB telah berfungsi sebagai pusat pendidikan untuk anak-anak yang bekerja di bawah batas hukum. Kedua Waktu yang diperlukan untuk menyelesaikan suatu tugas dapat dilaksanakan karena membantu sekolah anak PMI yang tidak mempunyai dokumen legal utnuk dapat sekolah di sekolah formal pemerintahan  Johor Bahru. Ketiga Besarnya biaya yang diperlukan beserta sumbernya adalah  tidak dikenakan biaya atau gratis. Sumber pembiayaan dari Pemerintah Indonesia , yaitu Kementerian Pendidikan dan Budaya ( Kemendikbud RI ) dan Kementerian Luar Negeri Kemenlu RI. Keempat kegiatan yang dilaksanakan adalah sesuai dengan Kurikulum pendidikan Kemendikbud RI di Indonesia. Khususnya di SIJB penting bagi siswa untuk dididik tentang nilai-nilai nasionalis, membantu mereka memahami identitas mereka sebagai warga negara Indonesia. Kelima sumber daya tersedia yaitu Guru sekolah Sekolah Indonesia di Luar Negeri termasuk SIJB direkrut , berada dibawah Kemenlu RI. Kepala sekolah SIJB adalah diplomat dari KJRI Johor Bahru. Abstract The objective of this research is to determine the "Effectiveness of the Indonesian Migrant Children's Education System (A Study at the Indonesian School of Johor Bahru)" by gathering field data on how the policy is implemented. Policy is defined here as a series of actions aimed at achieving specific goals within a particular environment, highlighting the obstacles and opportunities for implementing the proposed policy. This study employs a qualitative research method, presented in the form of descriptive information obtained from informants at the Indonesian School of Johor Bahru (SIJB), Malaysia. Conclusion The Indonesian Migrant Children's Education System at the Indonesian School of Johor Bahru (SIJB) has been found effective based on the fulfillment of five dimensions of effectiveness: First Goal Achievement: The school has successfully functioned as an educational hub for children of workers who are below the legal age limit. Second Timeliness: Tasks are executed efficiently, as the system provides a formal education pathway for children of Indonesian Migrant Workers (PMI) who lack the legal documentation required to attend Malaysian government schools. Cost and Funding: Education is provided free of charge. Funding is sourced from the Indonesian Government, specifically the Ministry of Education and Culture (Kemendikbud RI) and the Ministry of Foreign Affairs (Kemenlu RI). Activities: The curriculum aligns with the national standards set by the Indonesian Ministry of Education and Culture. At SIJB, there is a vital focus on nationalistic values to help students maintain their identity as Indonesian citizens. Resource Availability: Teachers at Indonesian Overseas Schools (SILN), including SIJB, are recruited and managed under the Ministry of Foreign Affairs. Furthermore, the Principal of SIJB serves as a diplomat from the Consulate General of the Republic of Indonesia (KJRI) in Johor Bahru.